Pembentukan Karakter Cerdas Finansial pada Siswa Sekolah Dasar melalui Pembelajaran Interaktif dan Simulasi Pasar Cilik - Tommy Kuncara; Immi Fiska Tarigan; Dessy Tri Anggraeni; Natallios Peter Sipasulta (Jurnal Abdi Masyarakat Multidisiplin, 2026)
Financial literacy should be introduced from elementary school age to develop economical, honest, disciplined, well-planned, and responsible financial behavior. This community service program aimed to improve students’ financial literacy while developing financially intelligent character through interactive learning and a Mini-Market Simulation. The program was conducted at SDN Margahayu XIII, Bekasi City, on June 15, 2026, involving 30 fifth-grade students, accompanying teachers, and an implementation team from Universitas Gunadarma. The program applied educational, participatory, contextual, and simulation-based approaches. The activities included a pre-test, interactive instruction on the value and functions of money, a needs-and-wants game, pocket-money allocation exercises, saving-goal preparation, price-setting practices, buying and selling transactions, change calculation, simple financial recording, a post-test, and program evaluation. The results showed that the students’ average financial literacy score increased from 53.0 in the pre-test to 86.4 in the post-test. This represented an improvement of 33.4 points or 63.0%. The percentage of students achieving the minimum score increased from 20.0% to 93.3%, while 96.7% of participants demonstrated improved scores. The greatest improvement was found in transaction skills and wise purchasing decisions.